(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
The project “Strengthening Civic Capacity for Sustainable Local Development in the Department of Choluteca” contributes to the training of citizens in the municipalities of Concepción de María, El Corpus, Choluteca, El Triunfo, Namasigüe, and San Marcos de Colón. The initiative addresses the need to promote and propose local development models through strategies and actions aimed at the sustainable and inclusive management of natural resources. It describes the design and implementation of a Political School aimed at community leaders, organizations, and officials, based on Participatory Action Research. The processes of management, participation, and capacity assessment are examined. Among the results, the formation of a local network, the creation of spaces for dialogue and advocacy, and the promotion of social oversight initiatives for sustainable territorial development stand out.